2021
DOI: 10.3390/molecules26237403
|View full text |Cite
|
Sign up to set email alerts
|

Study by Optical Spectroscopy of Bismuth Emission in a Nanosecond-Pulsed Discharge Created in Liquid Nitrogen

Abstract: Time-resolved optical emission spectroscopy of nanosecond-pulsed discharges ignited in liquid nitrogen between two bismuth electrodes is used to determine the main discharge parameters (electron temperature, electron density and optical thickness). Nineteen lines belonging to the Bi I system and seven to the Bi II system could be recorded by directly plunging the optical fibre into the liquid in close vicinity to the discharge. The lack of data for the Stark parameters to evaluate the broadening of the Bi I li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, Belmonte et al [139] have shown that the electron density in this kind of discharge is approximately 1×10 17 cm −3 , and the electron temperature is around 1 eV. For such a heavy element as bismuth, the electron temperature can be even lower (Te ~ 0.35 eV) [140].…”
Section: Comparison Of Dischargesmentioning
confidence: 91%
See 1 more Smart Citation
“…However, Belmonte et al [139] have shown that the electron density in this kind of discharge is approximately 1×10 17 cm −3 , and the electron temperature is around 1 eV. For such a heavy element as bismuth, the electron temperature can be even lower (Te ~ 0.35 eV) [140].…”
Section: Comparison Of Dischargesmentioning
confidence: 91%
“…Some of this energy is used to erode the electrodes, some is used to transform the liquid surrounding the discharge, and the rest is used to produce the discharge itself. It is also likely that pressure at ignition increases with the applied voltage and the electrical resistivity, with atmospheric pressure for glow discharge electrolysis exceeding typically 10 bars for submerged arcs in dielectric liquids [140] and probably in between for solution plasmas.…”
Section: Comparison Of Dischargesmentioning
confidence: 99%